Program Kepala Madrasah dalam Pembinaan Kompetensi Kepribadian Guru - Aini Safitri; Furqanisah Furqanisah (Yayasan Putroe Ceudah Aceh, 2026)
Teacher personality competency is expected to improve the teaching and learning process, the need for coaching carried out by the Madrasah principal in maintaining and improving personality competency. The purpose of this study is to qualitatively narrate what programs are implemented by the Madrasah principal in developing teacher competency including, the type of program, objectives, planning, implementation and evaluation applied by the Madrasah principal. The research method uses descriptive qualitative at MTsN 1 Aceh Besar. The sample of this study was the Madrasah principal, deputy Madrasah principal and 3 teachers. The data collection technique was with non-structured interviews. The data analysis technique used Miles & Humberment analysis. The results of the study obtained 3 programs in order to improve personality competency, including training, education and training motivation. The purpose of the program is to shape the character and ability of teacher communication skills in learning. In its implementation, the Madrasah principal makes a plan by making a needs analysis for program determination. At the implementation stage, the Madrasah principal determines the implementation schedule according to the effectiveness of the teacher's time at the Madrasah and evaluation has been carried out at the end of each program created and included in the employee performance appraisal.